The Implementation of Flipped Classroom Model to Improve the EFL Undergraduate Students’ Speaking Skills - Rina Rachmawati (Alsuna: Journal of Arabic and English Language, 2022)
Purpose - The research aims to determine whether there is a significant difference between undergraduate students in EFL speaking classes who implement the flipped classroom model and those who do not. Design/methodology/approach - The research was quantitative and classified as a quasi-experimental design. The data was taken from the scores of undergraduate students’ English speaking pre-test post-test and observation field notes. The test focused on the undergraduate students’ speaking performance and assessed using a speaking rubric. The data of both groups were analysed using an independent sample t-test. Findings/result - The experimental group’s post-test mean score (70.451) was higher than the control group (66.625). It could be assumed that there is a significant difference between the EFL undergraduate students’ speaking skills in the experimental and control groups. Originality/value - The flipped classroom model implementation offers an effective classroom model for EFL undergraduate students in improving their speaking skills. Paper type - Research paper